PENENTUAN ZONA POTENSI TINGKAT KERAWANAN BANJIR MENGGUNAKAN DATA PENGINDERAAN JAUH DAN SIG DI KALIMANTAN BARAT - Nanik Suryo Haryani (TATALOKA, 2012)
The aim of the research is to describe the zoning of the level of flood potential by the use of remote sensing data and Geographic Information System (GIS) in West Kalimantan Province. The applied methodology  is the weighing of flood indicators which are simultaneously form as flood variables. The result of study leads to the conclusion that flood sensitiveness could be classified into 4 category: very sensitive, sensitive, less sensitive, and not sensitive. The level of flood sensitiveness in West Kalimantan on rainy season shows that 4 regencies  area included in sensitive and very sensitive class, they are Singkawang , Pontianak, Sintang and Putussibau. The total area of very sensitive class in West Kalimantan is 29,713 hectares, and sensitive class 64,408 hectares.